Neutrophil-to-lymphocyte ratio as predictor of nausea and vomiting after elective laparoscopic cholecystectomy - Kumar Gupta, Amit; Rajput, Deepak (International Journal of Research in Medical Sciences, 2025)
Background: The neutrophil-lymphocyte ratio (NLR) or platelet-lymphocyte ratio (PLR) has been proposed as a parameter for the diagnosis of inflammatory diseases in different studies; however, the literature does not discuss this relationship for elective laparoscopic cholecystectomy. The purpose of this study was to determine whether preoperative NLR or PLR is associated with postoperative nausea and vomiting (PONV), one of the most common postoperative complications and whether it may act as a biomarker for the illness. Methods: The clinical data of 146 patients with symptomatic cholelithiasis who underwent elective laparoscopic cholecystectomy (ELC) at our institution were collected and analyzed. Results: We divided patients into PONV and No-PONV groups. and logistic regression analysis was used to identify predictors for PONV. In logistic regression analysis, the preoperative neutrophil-to-lymphocyte ratio (NLR) [odds ratio (OR): 1.61, 95% confidence interval (CI), p=0.01] was identified as an independent risk factor for the presence of PONV. On ROC analysis, the success of NLR in discriminating PONV was found to be statistically significant [area under curve (AUC)=0.631, p=0.01]. Conclusions: PONV can be predicted in patients undergoing ELC with NLR. As a result, blood parameters should be examined to enhance these patients’ post-operative recovery period.